The Role of Transformational Leadership Organisational Support and Work Experience as Efforts to Improve Employee Performance at Government Institution - Paramita, Olinda; Musoli (Journal of Organizational and Human Resource Development Strategies, 2024)
This study examines the partial effects of transformational leadership, organizational support, and work experience on employee performance. Transformational leadership boosts motivation and performance through shared vision, innovation, and individual attention. Organizational support, reflecting the organization's care for employee welfare, significantly impacts performance. Work experience is also critical for maximizing effectiveness.  The objective of this study is to evaluate the partial effects of transformational leadership, organizational support, and work experience on improving employee performance. The study surveyed 92 employees from Government Institution X using purposive sampling. Data analysis was conducted using SPSS 23. The findings show that transformational leadership (X1), organizational support (X2), and work experience (X3) each positively and significantly impact employee performance (Y). The findings emphasize the need for Government Institution X to enhance transformational leadership, strengthen organizational support, and provide training to improve work experience, thereby optimizing employee performance.